Why Are Indian Students So Angry? - Anonymous (International Higher Education, 2020)
A recent wave of student resistance is spreading across Indian campuses, as universities, with their liberal orientation, and the priorities of the Modi government, with its majoritarian and neoliberal agenda, clash against each other. The reaction of the government to university unrest is a cause for serious concern.